An in-depth study into the growth aspects and characteristic properties of ethyl 4-amino benzoate: a potential candidate for electro-optical applications. (4th September 2017) - Krishna, Anuj; Vijayan, N.; Sonia,; Vij, Mahak; Sridhar, B.; Soumya, H.; Singh, Budhendra; Das, Subhasis; Maurya, K. K.
Abstract : We present the bulk growth and characterization of an EPAB crystal using a single zone transparent resistive furnace. Abstract : In the present work we report the growth of a bulk size ethyl 4-amino benzoate crystal, a potential candidate for electro-optical applications, using an indigenously developed single zone transparent resistive furnace because of observed difficulties involved in its growth via a solution growth technique. The structure of the grown crystal was examined using single crystal X-ray diffraction and it was found that it crystallized in an orthorhombic crystal system with the non-centrosymmetric space group P 21 21 21 . The lattice parameters of the title material were further analysed using powder X-ray diffraction and they were found to be in agreement with the single crystal X-ray diffraction results. The strain in the lattice of the grown crystal was evaluated using the Hall–Williamson relation. The quality of the grown crystal was examined using a high resolution X-ray diffraction technique. Surface defects on the grown crystal were analysed using an etching technique. The transparency of the grown crystal was assessed using UV-vis spectroscopy and it was observed that the crystal possesses reasonably good transmittance over the visible spectrum. The optical band gap was also evaluated using Tauc's plot. Furthermore, the laser damage threshold value was calculated using a Nd:YAG laser. Moreover, the thermal parameters and mechanical properties of the grown crystal were evaluated using photopyroelectric and nano-indentation techniques and it was observed that the crystal possesses quite fair thermal stability, however, the mechanical strength was low. With reduction in defects as observed it could be a potential candidate for non-linear optical applications.